RANCANG BANGUN PURWARUPA TOILET PORTABLE BERDINDING PDLC DENGAN SISTEM SOLAR TRACKING BERBASIS ESP32 - Devia, Regina; Nugraha, Bayu; Pranita, Sri; Raka Agung, I GAP; Setiawan, I N (Jurnal SPEKTRUM, 2024)
Indonesia, as an archipelagic country in the Pacific region, is vulnerable to various natural disasters such as earthquakes, tsunamis, and volcanic eruptions. In such situations, infrastructure is often damaged or inaccessible. Therefore, a research team has designed an innovative sanitation solution in the form of a portable toilet with solar tracking and PDLC walls for disaster-prone evacuation areas. This Capstone Project aims to design a portable toilet that can generate independent electrical energy to operate the entire system within the toilet. The data collection methods involve observations and testing of hardware and software components, such as PIR sensors, ultrasonic sensors, DC voltage of 25 volts, ACS712 current sensors, I2C LCD display, and testing the accuracy of command timing from the NTP server sent by ESP32 to Arduino. Referring to research [5] where the solar panel angle can be adjusted by 20° every hour using LDR sensors, the research team developed the study using an NTP program that moves every hour from 09:00 to 17:00 to maximize solar energy absorption. A 20 Wp solar panel reaches its maximum power of 16.46 watts at 11:00 AM local time, and a 12V 9Ah battery can be used for 3 hours and 10 minutes with a 3 Ah load. This portable toilet can operate automatically and be monitored via a mobile phone. Further research is recommended to include detailed electronic component analysis and the implementation of a 2-axis tracking system.